Multi-omics analysis identified macrophages as key contributors to sex-related differences in ulcerative colitis - Fang, Xiaojie; Yang, Jiahao; Yang, Liu; Lin, Yiyou; Li, Yanyan; Yin, Xin; Dou, Xiaobing; Miao, Chenyun (Frontiers in Immunology, 2025)
BackgroundUlcerative colitis (UC) has a complex etiology, and whether there are sex-related differences in its molecular mechanisms remains unclear. This study employed multi-omics analysis to explore sex-based differences in UC, aiming to provide support for personalized treatment.MethodsThe GSE36807 and GSE206171 datasets from the GEO database were grouped by sex. Data were preprocessed using the R software, and DEGs identified using the limma package and key modules of WGCNA. LASSO regression was conducted to screen hub genes, ROC curves were used to evaluate diagnostic value, CIBERSORT was used to analyze immune cell proportions, and Spearman’s correlation was performed to explore associations. The single-cell dataset GSE214695 was processed using Seurat to analyze immune cell proportion differences. Histological, immunohistochemical, and metabolomic analyses were performed on the colon tissues of DSS-induced colitis model mice.ResultsThirty-seven DEGs and 47 co-expression modules were identified. LASSO regression highlighted RPS4Y1 as the core gene, which was significantly upregulated in males. Females showed higher proportions of resting NK cells and M0 macrophages but a lower number of eosinophils. RPS4Y1 expression was positively correlated with resting memory CD4+ T cells and eosinophils and negatively with M0 macrophages and resting mast cells. Macrophage function exhibited sex-based disparities. Increased immune cell infiltration was observed in female colon tissues compared with that in male colon tissues. Metabolomic analysis identified 140 sex-dimorphic metabolites, with significant alterations in glutathione metabolism.ConclusionRPS4Y1 exhibits sex-specific expression in UC and plays a key role in immunomodulation. Mitochondrial energy metabolism contributes to sex-based macrophage differences, highlighting the importance of considering sex-specific mechanisms in UC diagnosis and individualized treatment.